ANALISIS KADAR RESIDU PESTISIDA ORGANOFOSFAT PADA SAYURAN SERTA TINGKAT PERILAKU KONSUMEN TERHADAP SAYURAN YANG BEREDAR DI PASAR TRADISIONAL PRINGGAN KECAMATAN MEDAN BARU TAHUN 2015 - lulu marbun; nurmaini *; taufik ashar (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Pesticides organophosphate is a class of pesticides preferred by farmers because they havethe power exterminate strong, fast, and the result are clearly visible on the plant. Nevertheless organoposphate pestiside residues in humans can cause both acute and chronic poisoning, it is caused by the accumulative nature of residues of organophospate. This study aims to determine pesticide residues in vegetables as well as the level of consumer behaviors towards vegetables in Market Pringgan. Pesticides residues from the class of organophosphate is the active ingredient dimetoat, klorfirifos, profenofos, and triazofos researched on vegetables cabbage (Brassica oleracea), tomato (Solanum lypopersicum), carrot (Daucus carota), and long bean (Vigna sinensis). This study is a descriptive survey. The objects of the study incluced vegetables sold in Market Pringgan consisting of 4 samples then examined in Laboratorium Pengujian Mutu dan Residu Pestisida to know how much the residual pesticides in the vegetables. The result of the study referred to the SNI 7313:2008 MRL (Maximum Residue Limit) Product Agriculture. The samples were determined accidental sampling method, who bought the vegetables at observational location. This study found that residue of pestisides with active materials such as dimetoat, chlorpyriphos, profenofos, and triazofos were not detected in vegetables such as carrot and long bean. Result indicated that profonefos residue were found in carrot with content of 0,0188 mg/kg and result indicated that chlorpyriphos residue were found in cabbage with content 0,098 mg/kg. It is known that the levels of pesticide residues found in vegetables is still below the MRL of <0,5 mg/kg. Nevertheless, consumer are expected to be more careful in choosing vegetables.